1999
DOI: 10.1007/pl00007064
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Influences Growth and Production of Coumarins in Hairy Root Cultures of Witloof Chicory (Cichorium intybus L. cv. Lucknow Local)

Abstract: The effect of putrescine (Put) on the growth and production of two coumarins, esculin and esculetin, in hairy roots of chicory (Cichorium intybus L. cv. Lucknow local) was examined. To study the role of Put on growth and production of coumarins, polyamine inhibitors, namely alpha-dl-difluromethylornithine and alpha-dl-difluromethylarginine were used at 1 mM concentration. Put treatment at 1.5 mM produced a 1.9-fold increase in the growth of hairy roots, as well as the production of esculin and esculetin. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
1
11
0
2
Order By: Relevance
“…Putrescine, as a polyamine, enhanced growth and coumarin production in hairy root cultures of Cichorium intybus (Bais et al 1999) and the enhancement of betalaine production in hairy root cultures of Beta vulgaris by putrescine has also been reported (Suresh et al 2004). Increase in biomass and polysaccharide production in this study could be due to an increase in intracellular polyamine contents.…”
Section: Discussionsupporting
confidence: 46%
“…Putrescine, as a polyamine, enhanced growth and coumarin production in hairy root cultures of Cichorium intybus (Bais et al 1999) and the enhancement of betalaine production in hairy root cultures of Beta vulgaris by putrescine has also been reported (Suresh et al 2004). Increase in biomass and polysaccharide production in this study could be due to an increase in intracellular polyamine contents.…”
Section: Discussionsupporting
confidence: 46%
“…1) suggests that an active release of those substances is otherwise avoided, considering the Spm toxicity to bacteria (Tabor and Tabor 1985). The release of Put in both media may be seen as an interesting fact, once Bais et al (1999) showed that the addition of Put to the culture medium affected plant growth and production of metabolites in hairy root cultures.…”
Section: Resultsmentioning
confidence: 99%
“…1) by a comparison of its spectral data with those of an authentic sample. Esculetin has already been reported to be contained in Euphorbia lathyris L., [14][15][16] Fraxinus japonica Blume and Cichorium intybus L. [17][18][19][20] Many scientiˆc papers have also reported the pharmacological properties of esculetin such as anti-in‰ammatory eŠects, 17,21) antioxidative, 22) antiviral, 23) antimutagenic 24) and antiproliferative activities, 25) ultraviolet absorption eŠect, 26) and inhibition of lipoxygenase activity. [27][28][29] However, there is no report on the eŠect of esculetin against tyrosinase activity.…”
mentioning
confidence: 99%